A Novel Wheat-Rye 2R (2D) Disomic Substitution Line Pyramids Two Types of Resistance to Powdery Mildew - Han, Guohao (Plant disease, 2022)
Powdery mildew, caused by Blumeria graminis f. sp. tritici, is a devastating disease of wheat that seriously affects yield and quality worldwide. Because of the extensive growth of wheat cultivars with homogeneous genetic background, exploring novel resistant resources from wheat relatives has become important for increasing the genetic diversity of wheat. Rye (Secale cereale) is a wheat relative possessing abundant resistance genes because of its high variation. Wheat line AL69, resistant to powdery mildew, was developed by crossing, backcrossing, and self-pollination for multiple generations between hexaploid triticale Zhongsi 237 and common wheat cultivar Zimai 17. Through genomic in situ hybridization (GISH) and multicolor fluorescence in situ hybridization (FISH), nondenaturing FISH, multicolor GISH, and selection with specific molecular markers, AL69 was determined to be a wheat-rye 2R (2D) disomic substitution line. Testing with different B. graminis f. sp. tritici isolates and genetic analysis showed that the all-stage resistance (also called seedling resistance) of AL69 was conferred by the cataloged powdery mildew resistance gene Pm4b derived from Zimai 17, and its adult-plant resistance was derived from the alien chromosome 2R of Zhongsi 237, which was found to be different from the previously reported rye-derived Pm genes, including Pm7 on 2RL. In addition, AL69 showed improved spike number per plant, spike length, fertile spikelet number per spike, kernel number per spike, and grain yield per plant compared with its wheat parent Zimai 17. An elite line S251 combining powdery mildew resistance with excellent agronomic performance was selected from the progenies of AL69 and wheat cultivar Jimai 22. Therefore, AL69 has two types of resistance genes to powdery mildew and improved agronomic traits through pyramiding and thus can be used as a promising genetic stock for wheat breeding